EVALUASI DAYA DUKUNG LAHAN UNTUK TANAMAN PANGAN PADA LAHAN PERKEBUNAN TEMBAKAU RAKYAT DI LERENG TIMUR GUNUNG SINDORO - Rahayu Rahayu (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : Evaluation of Land Capability for Food Plants at Rural Tobacco Area in East Part of Sindoro Mountain. This research was conduct at east part of Sindoro Mountain in Central Java with elevation around  1,000 – 2,000 m. Observation  showed  land degradation  occurred  in this location.  This research was to know decreasing of land quality of tobacco area and the possibility of this area for  food  plants  production  as  tobacco  substitution.  The  steps  of  research  were  soil  survey, laboratory  analysis  and  plotting  of land characteristics  into food  plants  requirements.  Results showed  that  the soils  of area  are  Entisols  and  Andisols  with  slope  of 8 to 30%.  GIS  analysis resulted  in 5 land  unit  areas.  Land  suitability  for  tobacco  is marginally  suitable  (S3)  and  not suitable (N) with limiting factors are precipitation, soil solum, pH H2O, C‐organic and slope. Land suitability for corn is marginally suitable (S3) and not suitable (N) with limiting factors are precipitation, soil solum, pH H2O, C‐organic and slope. Land suitability for cassava is not suitable (N) with limiting factors are soil solum and slopes. All of land unit areas have limiting factor for tobacco and food plants. Degradation of land resulted in decrease of quantity yield of tobacco.Keywords: food plants, land, soil degradation, tobacco